2018
DOI: 10.7554/elife.25801
|View full text |Cite
|
Sign up to set email alerts
|

Replication Study: Fusobacterium nucleatum infection is prevalent in human colorectal carcinoma

Abstract: As part of the Reproducibility Project: Cancer Biology, we published a Registered Report (Repass et al., 2016), that described how we intended to replicate an experiment from the paper ‘Fusobacterium nucleatum infection is prevalent in human colorectal carcinoma’ (Castellarin et al., 2012). Here we report the results. When measuring Fusobacterium nucleatum DNA by qPCR in colorectal carcinoma (CRC), adjacent normal tissue, and separate matched control tissue, we did not detect a signal for F. nucleatum in most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 31 publications
3
41
0
Order By: Relevance
“…Thus, it was not surprising that tissue-based studies did not provide clearer associations between the mucosal microbiota and the presence of tumors. Interestingly, Fusobacterium , which has received increased attention for its potential role in tumorigenesis ( 6 ), was not consistently identified across the studies in our meta-analysis, which is consistent with a recent replicability study ( 36 ). This could be due to the relatively small number of individuals in the limited number of studies.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, it was not surprising that tissue-based studies did not provide clearer associations between the mucosal microbiota and the presence of tumors. Interestingly, Fusobacterium , which has received increased attention for its potential role in tumorigenesis ( 6 ), was not consistently identified across the studies in our meta-analysis, which is consistent with a recent replicability study ( 36 ). This could be due to the relatively small number of individuals in the limited number of studies.…”
Section: Discussionsupporting
confidence: 90%
“…Cynthia L Sears was the Reviewing Editor for the Registered Report ( Repass et al, 2016 ) and the Replication Study ( Repass and Reproducibility Project: Cancer Biology, 2018 ).…”
Section: Notementioning
confidence: 99%
“…In 2016, as part of the Reproducibility Project: Cancer Biology , Repass et al published a Registered Report which explained in detail how they would seek to replicate the experiment (figure 2 in Castellarin et al) in which quantitative polymerase chain reaction (qPCR) was used to detect F. nucleatum in colon tissues taken from colon cancer patients ( Repass et al, 2016 ). The results of this experiment have now been published as a Replication Study ( Repass and Reproducibility Project: Cancer Biology, 2018 ). In short, F. nucleatum was detected in just 25% of colorectal carcinomas in the Replication Study, and the difference in the level of this species in colorectal carcinomas and adjacent tissues (there was 10% more F. nucleatum in the carcinomas) was not significant.…”
mentioning
confidence: 99%
“…It has been confirmed that F. nucleatum contributes to the carcinogenesis of colorectal cancer by inducing inflammation and inhibiting host immunity (Feng et al, 2019;Wu et al, 2019). There is evidence that F. nucleatum induces the production of microbial peptides that upregulate the expression of proinflammatory cytokines and tumor necrosis factor and disrupt homeostasis and host defense barriers (Krisanaprakornkit et al, 2000;Repass et al, 2018). An F. nucleatum strain isolated from IBD patients showed upregulation of monocyte chemoattractant protein Mice (n = 5 per group) were administered F. nucleatum or PBS for 2 weeks and treated with 3% dextran sulfate sodium (DSS) for 7 days.…”
Section: Discussionmentioning
confidence: 95%